The Religion of Confrontation: Concepts, Violence, and Scholarship - Levene, Nancy (Harvard theological review, 2020)
Jonathan Z. Smith's essay “Religion, Religions, Religious” discovers the invention of religion as a generic term in colonial adventure. The move is notable: religion is born in violence, but it can be repurposed as a term without determinate content by which to compare cases. Smith's origin story is to empower scholars to pick up “religion” as they do the terms “language” and “culture.” There are reasons, however, not only to revisit the story but also to ask whether it is not missing a move—whether the reclamation of a violent term requires more from the scholar than Smith's structuralist reversal, his reinvention of colonialist invention. I compare Smith's resourcefulness with the conquistadors to Edward Said's critique of Orientalism. Both thinkers are asking questions of violence, invention, and use. Said more squarely addresses problems of thinking with and beyond guilty concepts. Yet Smith's story is an important counterpoint. Together, these thinkers help the humanities lay ground for a more expansive and self-conscious theoretical future.